Assimilate limitation compensating factors under environmental stresses in wheat - Thakur, Vidisha; Rane, Jagadish (Journal of Cereal Research, 2021)
In recent years, considerable efforts have been made to understand the factors controlling grain weight in wheat. In addition to sink capacity, the supply of assimilates for developing grain determines the weight of the grain. The current photosynthesis of the flag leaf is the most important source of assimilation, and the onset and rate of senescence are important factors for determining grain yield. Hence stress induced leaf senescence can reduce the supply of assimilates for grains. Under such conditions, assimilate contributions of stored non structural carbohydrates in stem and photosynthesis of non foliar parts of the plant such as spike are crucial for grain development. Non structural carbohydrates in wheat stem have been estimated and efforts have been made to reveal the mechanisms of assimilate partitioning. The hormone levels and activities of enzymes involved in assimilate partitioning and carbohydrate metabolism in wheat stem and grains have been significantly correlated with grain filling in wheat. Remobilization efficiency of stem reserves is increased under heat or drought stress along with increase in the proteins associated with senescence and ROS handling in the tolerant cultivars. The heat and drought tolerant wheat cultivars have a higher WSC content in stem, higher mobilization efficiency, longer duration of grain filling and stronger sink activity. However, some of the key issues such as intra-spike assimilation distribution have not been sufficiently addressed. This review has been compiled for information related to assimilate supply to the developing wheat grain under stress conditions and also enlists opportunities to translate this knowledge into traits for improvement of climate resilience in wheat.